Pengembangan Spiritual Anak-Anak Madrasah Ibtidaiyah Melalui Program Festival Anak Sholeh 2023 - Nuri, Rafita; Noorhalida, Noorhalida; Rahmah, Fadilatur; Jannah, Raudatul; Andani, Rizkia; Fitriana, Fitriana; Pransiska, Nadia; Nasrullah, Nasrullah; Arzaq, Farid Basithul; Fadillah, Haris (MENARA RIAU, 2024)
Spiritual Development of Madrasah Ibtidaiyah Children is an important aspect in forming the character of the younger generation. This research explores the efforts made in Kalampangan Subdistrict to improve the spiritual dimension of children through the 2023 Sholeh Children's Festival Program. This research aims to understand the impact of this program on the spiritual development of elementary school children in the area. This research method uses PAR (Participatory Action Research) by involving all members of KKN group 89 A and the Kalampangan community by holding a competition to measure changes in the understanding of spiritual, moral and ethical values among elementary/MI children. The research results show that the 2023 Sholeh Children's Festival Program has a significant positive impact in increasing children's spiritual awareness, developing a sense of empathy, and strengthening good values. This research makes an important contribution to understanding how programs such as the 2023 Sholeh Children's Festival can be an effective means of building the spiritual foundations of children at the Madrasah Ibtidaiyah level.